PEREDARAN NARKOBA DI SELAT MALAKA DAN KEPULAUAN RIAU - Ginting, I Viola Sandra; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study aims to discuss the general description of the Malacca Strait and Riau Archipelago along with cases of drug trafficking that occur in these areas. As for the discussion related to drugs, it consists of history, types, consequences and smuggling techniques carried out by the perpetrators. This research is a descriptive qualitative research. Data collection techniques in this study were through literature study from several books, journals, articles, news, documents, and websites. The theory used is the concept of transnational crime which is a form of crime that poses a serious threat to global security, welfare and prosperity because the nature of this crime involves many countries. The characteristic of transnational crimes is that they can cross national boundaries so that they have an impact on the security and economic stability of the country concerned. The results of this study can be concluded that the waterways of Indonesia, precisely in the Malacca Strait and Riau Archipelago, are areas that are prone to drug smuggling. This drug smuggling technique also takes advantage of coastal communities who live in the area with economic motives. This crime has become a threat because the losses caused are enormous, especially if it can affect the quality of the nation's generation. Keywords: drug trafficking, Malacca Strait, Riau Islands, transnational crime